International Short Course in Pictures: Utilizing Photovoice to Promote an Indonesian Student's Intercultural Awareness - Arini Nurul Hidayati; Widia Yunita; Fuad Abdullah (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2022)
Capturing moments through photos has now become a common phenomenon in various circles, including academics. It aims to perpetuate every historical value in the life of an individual. In this article, the authors attempt to explore how an Indonesian student experienced her inaugural intercultural journey during a two-month short course program in Ireland, a pathway program to prepare prospective Ph.D students with academic and social skills, through photographs that she took amid the program. This perspective of intercultural travel is embedded in the personal and cultural identities of the participant. This article uses photovoice analysis to exemplify how the participant negotiated her natural identities, institutions, discourses, and affinities during intercultural interaction. The data used in this study are photographs taken by the participant and her voices on those photos guided by the SHOWeD model. The authors employed Pierce’s semiotic approach to scrutinize the symbols, icons, and indexes contained in the Photovoice. The results of the analysis indicate that the participant experienced a plethora of moments that aroused her intercultural awareness, starting from managing the initial self-conflicts, adjusting in the fast-paced academic culture by interacting with cultural actors, and responding positively to all stimuli that came during intercultural interactions. Needless to say, challenges are also present as self-development reinforcement. However, this constraint was considered as a self-defense mechanism and an attempt to respect the self, not as a failure of intercultural interaction. In conclusion, the student is currently no longer a cultural observer and imitator, but rather a cultural actor.